Marketing Mix Impact on Scarlett Whitening Purchase Decisions in Banda Aceh - Pujiastuti, Nur; Elaña, Relanie Jean; Mansueto, Vinus Mae (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: This study aims to analyze the influence of promotion, price, and product quality on the purchasing decisions for Scarlett Whitening products in Banda Aceh. A key objective is to identify which of these three factors exerts the most dominant effect on consumer behavior in this regional context. Methodology: Employing a quantitative explanatory design, data were collected via a survey. A structured questionnaire was distributed to 100 consumers selected through purposive sampling. Multiple linear regression analysis was performed using IBM SPSS Statistics 25. Prior to hypothesis testing, instrument validity and reliability were confirmed, and classical assumption tests (normality, multicollinearity, heteroscedasticity) were conducted to ensure the robustness of the regression model. Main Findings: The results confirm that promotion, price, and product quality each have a positive and significant partial effect on purchasing decisions. Product quality is identified as the most influential variable. Simultaneously, the three variables significantly affect consumer decisions (F(3, 96) = 54.78, p < .001), with the model explaining 62% of the variance in purchase behavior (R² = .62). Novelty/Originality of this study: This study contributes to the marketing literature by empirically establishing a hierarchy of marketing mix effectiveness for a fast-moving consumer goods (FMCG) cosmetic brand in an emerging regional market. It specifically highlights the paramount importance of product quality over price and promotion in driving consumer loyalty within the local context of Banda Aceh, offering nuanced insights for localized brand strategy.